Structure-activity relationship study of a series of caspase inhibitors containing γ-amino acid moiety for treatment of cholestatic liver disease. Issue 10 (1st June 2018) - Mou, Jianfeng; Wu, Songliang; Luo, Zhi; Guo, Fengying; He, Haiying; Wang, Jianhua; Lin, Fusen; Guo, Fengxun; Sun, Jianping; Shen, Liang; Zeng, Minggao; Wang, Chuan; et al.
Graphical abstract: Highlights: A series of caspase inhibitors containing γ-amino acid moiety have been synthesized. Several derivatives showed promising efficacy in cell-based Jurkat/Fas (JFas) assays. Compound 20o demonstrated ameliorating total bilirubin efficacy in an ANIT cholestatic model. Abstract: A series of caspase inhibitors containing γ-amino acid moiety have been synthesized. A systemic study on their structure-activity relationship of anti-apoptotic cellular activity is presented. These efforts led to the discovery of compound 20o as a potent caspase inhibitor, which demonstrated preclinical ameliorating total bilirubin efficacy with a significantly improved pharmacokinetic profile.